Phytochemical screening, total phenolic, reducing sugar contents, and antioxidant activities of Gelidium spinosum (S.G. Gmelin) P.C. Silva - Warsi, Warsi; Jaswir, Irwandi; Khatib, Alfi; Ahmed, Qamar Uddin; Nawi, Mohamed Sufian B.M.; Rohman, Abdul; Narwanti, Lin (Faculty of Pharmacy, University of Benin, 2023)
Gelidium spinosum is edible red seaweed with high economic values and potential pharmacological activities. This research aimed to evaluate phytochemicals, total phenolic content, reducing sugar content, and antioxidant properties of Gelidium spinosum methanol-aqueous extracts. Maceration with different solvent ratios of methanol-water was employed to afford various crude extracts. The standard procedures of preliminary phytoconstituents determination were employed to screen the presence of various phytochemicals. Phenolic and reducing sugar contents were determined using Folin-Cioucalteu and 3,5-dinitro salicylic acid methods. The antioxidant activities of seaweed extracts were determined through DPPH and reducing power assays. The 100% methanol extract of G. spinosum was found to be rich in alkaloids, flavonoids, glycosides, polyphenols, proteins, reducing sugar, saponins, steroids and tannins. The aqueous extract of G. spinosum contained flavonoids, glycosides, polyphenols, reducing sugars, saponins and tannins at a moderate level. The total phenolic content range was 6.43 to 49.78 mg EGA/g extract. The highest reducing sugar content was shown by 100% methanol extract (1278.20 ± 21.25 mg GE/g extract). The highest antioxidant activities were found in 100% methanol extract for reducing power assay, and 75% methanol extract of G. spinosum for DPPH method. There was a positive correlation between reducing sugar, total phenolic contents and antioxidant activities. Results further confirmed the potential use of red seaweed in various ailments, however, should further be confirmed through more appropriate similar studies.